Asking patients about their religious and spiritual beliefs: Cross-sectional study of family physicians - Lee-Poy, Michael (Can Fam Physician, 2016)
OBJECTIVE: To examine family physicians’ practices in and opinions on asking patients about their religious and spiritual beliefs, as well as physicians’ comfort levels in asking. DESIGN: Cross-sectional study using self-administered questionnaires. SETTING: Kitchener-Waterloo, Ont. PARTICIPANTS: A total of 155 family physicians with office practices. MAIN OUTCOME MEASURES: Frequency of asking patients about their religious and spiritual beliefs and physicians’ comfort levels in asking. Separate multiple linear regression analyses were conducted for each of these outcomes. RESULTS: A total of 139 questionnaires were returned for a response rate of 89.7 %. Of the respondents, 51.8 % stated that they asked patients about their religious and spiritual beliefs sometimes. Physician opinion that it was important to ask patients about religious and spiritual beliefs (P = .001) and physician comfort level with asking (P < .001) were significantly associated with physicians’ frequency of asking patients about their religious and spiritual beliefs. Comfort level with asking patients about their religious and spiritual beliefs was significantly associated with the opinions that it was important to ask (P = .004) and that it was their business to ask (P = .003), as well as with lack of training as the reason for not asking (P = .007). CONCLUSION: This study found that family physicians were more likely to ask patients about their religious and spiritual beliefs if they had higher comfort levels in asking or if they believed that asking was important. Further, this study found that family physicians’ comfort level with asking was higher if they believed that it was important to ask and that it was their business to ask about religious and spiritual beliefs. Physician comfort levels with asking patients about religious and spiritual beliefs can be addressed through adequate training and education.